2004
DOI: 10.1110/ps.04947204
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative aggregation of α‐synuclein requires tyrosines

Abstract: Abstract␣-Synuclein is the main component of the intracellular protein aggregates in neurons of patients with Parkinson's disease. The occurrence of the disease is associated with oxidative damage. Although it is known that peroxidative chemistry leads to the aggregation of ␣-synuclein in vitro, the specific amino acid types of ␣-synuclein involved in this type of aggregation have not been identified. We show, using human cytochrome c plus H 2 O 2 as the source oxidative stress, that the tyrosines of ␣-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…because of the lack of reactive and accessible Tyr residues in a protein). Notably, the presence of Tyr residues is essential for aggregation of Syn and LB formation as well as for its involvement in cross-linking through a catalytic peroxidase process (53), in line with our findings on protein-derived (Tyr ⅐ ) radicals in oligomers and high molecular weight aggregates.…”
Section: Discussionsupporting
confidence: 90%
“…because of the lack of reactive and accessible Tyr residues in a protein). Notably, the presence of Tyr residues is essential for aggregation of Syn and LB formation as well as for its involvement in cross-linking through a catalytic peroxidase process (53), in line with our findings on protein-derived (Tyr ⅐ ) radicals in oligomers and high molecular weight aggregates.…”
Section: Discussionsupporting
confidence: 90%
“…Several in vitro studies of aS have shown the relevance of tyrosine residues to the oxidation-induced formation of covalent aggregates, in which stable covalent interprotein -C-C-bonds in the form of dityrosine (diTyr) groups are implicated [11,12]. DiTyr has also been identified as an oxidative stress marker in brain tissue models of PD [13].…”
mentioning
confidence: 99%
“…Considering that oxidative stress is one of the major factors linked to PD, oxidation of aS residues is a pathway to be considered. In previous studies, the specific oxidation of side-chain tyrosine of aS was achieved by peroxidative or peroxynitrile chemistry, leading to the formation of n-mers (n Z2) as well as lower molecular breakdown products [11,12,15,26,27]. Other oxidative stress models based on Fenton chemistry (i.e., a transition metal/H 2 O 2 or enzyme/H 2 O 2 systems) have also been extensively employed to reproduce in vitro aS covalent aggregation, but these systems are less specific in that they induce other modifications of amino acid residues, as in the case of Cu 2 þ þH 2 O 2 [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional role for the peroxidase activity of cyt c has been recently proposed in the study of the oxidative stressinduced aggregation of -synuclein, a "natively unfolded" protein constituting the major component of intracellular inclusions in several neurodegenerative disorders, such as Parkinson's disease [82,83]. Recently, some authors have observed the formation of millimeter-length fibers of phospholipid vesicles-bound cyt c displaying amyloid (ß-sheet) characteristics [84]; this implies that the cyt c-phospholipids interaction may play a role in some of the disorders attributed to amyloid formation, such as AA-amyloidosis and Alzheimer's disease.…”
Section: Cytochrome C: Non-native Conforma-tions and Distinct Biologimentioning
confidence: 99%